Intravitreal Gene Therapy vs. Natural History in Patients With Leber Hereditary Optic Neuropathy Carrying the m.11778G>A ND4 Mutation: Systematic Review and Indirect Comparison - Newman, Nancy J.; Yu-Wai-Man, Patrick; Carelli, Valerio; Biousse, Valerie; Moster, Mark L.; Vignal-Clermont, Catherine; Sergott, Robert C.; Klopstock, Thomas; Sadun, Alfredo A.; Girmens, Jean-François; La Morgia, Chiara; DeBusk, Adam A.; et al. (Frontiers in Neurology, 2021)
Objective: This work aimed to compare the evolution of visual outcomes in Leber hereditary optic neuropathy (LHON) patients treated with intravitreal gene therapy to the spontaneous evolution in prior natural history (NH) studies. Design: A combined analysis of two phase three randomized, double-masked, sham-controlled studies (REVERSE and RESCUE) and their joint long-term extension trial (CLIN06) evaluated the efficacy of rAAV2/2-ND4 vs. 11 pooled NH studies used as an external control. Subjects: The LHON subjects carried the m.11778G>A ND4 mutation and were aged ≥15 years at onset of vision loss. Methods: A total of 76 subjects received a single intravitreal rAAV2/2-ND4 injection in one eye and sham injection in the fellow eye within 1 year after vision loss in REVERSE and RESCUE. Both eyes were considered as treated due to the rAAV2/2-ND4 treatment efficacy observed in the contralateral eyes. Best corrected visual acuity (BCVA) from REVERSE, RESCUE, and CLIN06 up to 4.3 years after vision loss was compared to the visual acuity of 208 NH subjects matched for age and ND4 genotype. The NH subjects were from a LHON registry (REALITY) and from 10 NH studies. A locally estimated scatterplot smoothing (LOESS), non-parametric, local regression model was used to modelize visual acuity curves over time, and linear mixed model was used for statistical inferences. Main Outcome Measures: The main outcome measure was evolution of visual acuity from 12 months after vision loss, when REVERSE and RESCUE patients had been treated with rAAV2/2-ND4. Results: The LOESS curves showed that the BCVA of the treated patients progressively improved from month 12 to 52 after vision loss. At month 48, there was a statistically and clinically relevant difference in visual acuity of −0.33 logarithm of the minimal angle of resolution (LogMAR) (16.5 ETDRS letters equivalent) in favor of treated eyes vs. NH eyes (p < 0.01). Most treated eyes (88.7%) were on-chart at month 48 as compared to 48.1% of the NH eyes (p < 0.01). The treatment effect at last observation remained statistically and clinically significant when adjusted for age and duration of follow-up (−0.32 LogMAR, p < 0.0001). Conclusions: The m.11778G>A LHON patients treated with rAAV2/2-ND4 exhibited an improvement of visual acuity over more than 4 years after vision loss to a degree not demonstrated in NH studies. Clinical Trial Registration: NCT02652767, NCT02652780, NCT03406104, and NCT03295071.